2015
DOI: 10.3389/fpsyg.2015.00014
|View full text |Cite
|
Sign up to set email alerts
|

The Trier Social Stress Test as a paradigm to study how people respond to threat in social interactions

Abstract: In our lives, we face countless situations in which we are observed and evaluated by our social interaction partners. Social-evaluative threat is frequently associated with strong neurophysiological stress reactions, in particular, an increase in cortisol levels. Yet, social variables do not only cause stress, but they can also buffer the neurophysiological stress response. Furthermore, social variables can themselves be affected by the threat or the threat-induced neurophysiological stress response. In order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(76 citation statements)
references
References 92 publications
(229 reference statements)
2
71
0
3
Order By: Relevance
“…Third, we used a laboratory‐based stress induction procedure, the TSST, rather than a personalized, naturalistic procedure. The extensive literature on the TSST and its demonstrated ability to elevate cortisol levels in most subjects validates its use (Frisch et al., ). Finally, a larger sample size would have enabled a more comprehensive look at sex differences, although sex is included as a covariate in our analyses.…”
Section: Discussionmentioning
confidence: 97%
“…Third, we used a laboratory‐based stress induction procedure, the TSST, rather than a personalized, naturalistic procedure. The extensive literature on the TSST and its demonstrated ability to elevate cortisol levels in most subjects validates its use (Frisch et al., ). Finally, a larger sample size would have enabled a more comprehensive look at sex differences, although sex is included as a covariate in our analyses.…”
Section: Discussionmentioning
confidence: 97%
“…In fact, little work exists on the link between social support and cortisol reactivity in general. Frisch, Häusser, and Mojzisch (2015) reviewed the available work on social support and cortisol responses to a psychosocial laboratory stressor (Trier Social Stress Test) and concluded that attenuation of cortisol reactivity by social support involves important moderators like sex, attachment style, cultural background, and personality of the person receiving support. Thus, while this small literature does not directly address how these moderating effects influence perinatal depression risk, it suggests the possibility that social support might be protective, given its mitigating role in cortisol reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…This reaction is also called the sympathetic-adrenal-medullary (SAM) axis [35] and aims at the capacity to “fight-fright-or-flight.” It concentrates the resources of the organism on the necessary organs to fight or flight, increasing the blood flow to the heart and skeletal muscle, the metabolic rate, the blood pressure, and the respiration [1]. …”
Section: Resultsmentioning
confidence: 99%